MODIFIED APPROACH TO ENSURE A UNIFORM LAYER OF ELASTIC MATERIAL FOR RELINING COMPLETE DENTURES WITH SELF CURING SILICONES - Mariana Yankova; Bozhidar Yordanov; Mariana Dimova-Gabrovska; Todor Peev (Journal of IMAB, 2019)
Setting the Problem: In the available literature, the preparation of the removable denture for the relining procedure is subjective. It is not possible to ensure a uniform thickness of the relining material in all zones, with the risk of unwanted alteration of the previously determined registrations – occlusal plane, occlusal vertical dimension and interocclusal relationship. Purpose: The basic purpose of this article is to propose a clinically and laboratory tested method for relining complete dentures with a uniform layer of elastic material and preserving of all clinicаlly determined registrations. Materials and Method: To create a space and ensure a uniform layer of elastic relining material, a vacuum shaped polypropylene space maintainer is fabricated. This clinical approach is illustrated by presenting a selected clinical case with retentive maxillary tuberosities and severe mandibular bone atrophy. Results and Discussion: The fabrication of a space maintainer for indirect relining of complete dentures with cold-curing silicones ensures a uniform layer of elastic relining material. The space maintainer is positioned in place during all clinical and laboratory steps, preserving in this way the clinically determined registrations – occlusal plane level, occlusal vertical dimension and intermaxillary relations. Conclusions: The proposed clinical and laboratory method for relining complete dentures with cold-curing silicones is rational and effective. The space-maintainer secures a uniform layer of relining material, even distribution of masticatory pressure to the mucosal-bone biologic base and protects the denture against fracturing.